Culture density influences the functional phenotype of human macrophages - Ruder, Adele V.; Temmerman, Lieve; van Dommelen, Joep M.A.; Nagenborg, Jan; Lu, Chang; Sluimer, Judith C.; Goossens, Pieter; Biessen, Erik A.L. (Frontiers in Immunology, 2023)
Macrophages (MΦ) are commonly cultured in vitro as a model of their biology and functions in tissues. Recent evidence suggests MΦ to engage in quorum sensing, adapting their functions in response to cues about the proximity of neighboring cells. However, culture density is frequently overlooked in the standardization of culture protocols as well as the interpretation of results obtained in vitro. In this study, we investigated how the functional phenotype of MΦ was influenced by culture density. We assessed 10 core functions of human MΦ derived from the THP-1 cell line as well as primary monocyte-derived MΦ. THP-1 MΦ showed increasing phagocytic activity and proliferation with increasing density but decreasing lipid uptake, inflammasome activation, mitochondrial stress, and secretion of cytokines IL-10, IL-6, IL-1β, IL-8, and TNF-α. For THP-1 MΦ, the functional profile displayed a consistent trajectory with increasing density when exceeding a threshold (of 0.2 x 103 cells/mm2), as visualized by principal component analysis. Culture density was also found to affect monocyte-derived MΦ, with functional implications that were distinct from those observed in THP-1 MΦ, suggesting particular relevance of density effects for cell lines. With increasing density, monocyte-derived MΦ exhibited progressively increased phagocytosis, increased inflammasome activation, and decreased mitochondrial stress, whereas lipid uptake was unaffected. These different findings in THP-1 MΦ and monocyte-derived MΦ could be attributed to the colony-forming growth pattern of THP-1 MΦ. At the lowest density, the distance to the closest neighboring cells showed greater influence on THP-1 MΦ than monocyte-derived MΦ. In addition, functional differences between monocyte-derived MΦ from different donors could at least partly be attributed to differences in culture density. Our findings demonstrate the importance of culture density for MΦ function and demand for awareness of culture density when conducting and interpreting in vitro experiments.